2019
DOI: 10.2516/ogst/2019011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity on the properties of the different HPAM/Al3+systems

Abstract: In order to achieve oil increment and water cut reduction in the heterogeneous oil reservoirs, a conformance control technology by using HPAM/Al 3+ systems has been widely used due to the low price and environmental friendliness. However, the complex structure and state of high-valent metal ions in brine water can directly affect the properties of the different HPAM/Al 3+ systems, which may lead to unreasonable applications. Therefore, in order to better utilize the HPAM/Al 3+ systems, the characteristics of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…The logarithm data of GT in this study is extracted and fitted to the reciprocal of absolute temperature, and the plot of ln(GT) vs. 1/T is given in Figure 9. The data of GT are fitted well with Equation (8). The activation energies of two formulas were calculated to be 51.91 and 55.45 kJ/mol, respectively.…”
Section: Effect Of Temperaturementioning
confidence: 88%
See 1 more Smart Citation
“…The logarithm data of GT in this study is extracted and fitted to the reciprocal of absolute temperature, and the plot of ln(GT) vs. 1/T is given in Figure 9. The data of GT are fitted well with Equation (8). The activation energies of two formulas were calculated to be 51.91 and 55.45 kJ/mol, respectively.…”
Section: Effect Of Temperaturementioning
confidence: 88%
“…The hydrolyzed polyacrylamide contains many amide groups (-CONH 2 ) and carboxyl groups (-COO − ) in its molecular chain. It could crosslink with different types of crosslinkers, such as Cr 3+ [ 6 , 7 ], Al 3+ [ 8 ], Zr 4+ [ 9 ], phenolic resin [ 10 , 11 ], etc. However, multivalent metal ions and phenolic resin are toxic.…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 While pH and temperature have the most significant effect on the gelation time, other factors influence the equilibrium gel strength such as the salt type and content and the polymer to crosslinker ratio. 27 , 33 , 35 …”
Section: Introductionmentioning
confidence: 99%
“…Another factor that affects the stability of colloidal crosslinkers is the type of additives in the system where recent studies showed that silica nanoparticles can enhance both the thermal as well as physical stabilities of micro-sized particles in the polymeric solutions. , Apart from the stability of particles, crosslinking of the inorganic crosslinkers was found to be pH-triggered, having the gelation time decreased as the pH increases . The effect of pH is believed to result from the hydrolysis of PAM that is increased at high pH, leading to the conversion of more amide groups to carboxylate groups resulting in more crosslinkable sites. , Moreover, the crosslinking reaction follows Arrhenius’s equation where the increase in the temperature increases the crosslinking rate. , While pH and temperature have the most significant effect on the gelation time, other factors influence the equilibrium gel strength such as the salt type and content and the polymer to crosslinker ratio. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The polyacrylamide contains a large number of amide groups (-CONH2) and carboxyl groups (-COO -) in its molecular chain after hydrolysis. It could crosslink with different types of crosslinkers, such as Cr 3+ [6,7], Al 3+ [8], Zr 4+ [9] or phenolic resin [10][11] et al. However, multivalent metal ions and phenolic resin are toxic.…”
Section: Introductionmentioning
confidence: 99%